Modified positive electrode material and preparation method thereof, positive electrode sheet and battery
By doping silicates and/or tellurites into high-nickel ternary materials and coating organic lithium salts to form a modified ternary positive electrode material, the problem of structural degradation of high-nickel ternary materials during long cycles is solved, and the rate performance and cycling performance are significantly improved.
Patent Information
- Application Number
- CN202411127416.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-08-16
AI Technical Summary
During the long cycle, high-nickel ternary materials have frequent expansion and contraction, resulting in structural deterioration, reduced conductivity, increased impedance, and affected rate performance and cyclic performance.
By doping silicates and/or tellurites in high nickel ternary materials, a modified ternary positive electrode material is formed, with the chemical formula of Li(1-2a) NixCoyMnzO2A2a (BO3)a, A includes K and/or Na, B includes Si and/or Te, partly doped in the body phase, partly forming solid solution doping on the surface, and coated with organic lithium salt.
It inhibits cracking of the cathode material particles during the circulation process, enhances structural stability, improves rate performance and circulation performance, and reduces the impact of the corrosion of the electrolyte solution on the cathode material.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a modified positive electrode material and a preparation method thereof, a positive electrode sheet and a battery. Background Art
[0002] Lithium-ion batteries are widely used in digital products such as laptops, mobile phones, and electric vehicles due to their high energy density, recyclability, and long life. x Co y Mn z O2 (NCM) (x+y+z=1, x≥0.8) and LiNi x Co y Al z O2 (NCA) (x+y+z=1, x≥0.8) is considered to be a cathode material with great development potential because it has the advantages of extremely high theoretical capacity, high energy density, high operating voltage and low cost compared with other cathode materials.
[0003] Due to the increase of Ni content in high nickel ternary materials, for example, for NCM, the proportion of Co and Mn in the composition decreases. Because Co has higher electronic conductivity, it helps to improve structural stability and conductivity, while Mn is usually Mn in the process of charge and discharge. 2+ It exists in the NCM bulk phase, which helps to improve the structural stability and thermal stability. Therefore, the structural stability and thermal stability of high-nickel ternary materials decrease with the increase of Ni content. During the long cycle of the battery, as the de-lithiation and lithium insertion proceed, the particles of the high-nickel ternary material frequently expand and contract, the internal stress of the particles increases, resulting in cracks, and then forming new interfaces. The internal conductivity of the particles is weakened, and the impedance increases. At the same time, a large amount of electrolyte is consumed to generate a new cathode-electrolyte interface (CEI) film at the new interface, which will have a serious impact on the rate performance and cycle performance. Summary of the invention
[0004] In view of this, the embodiments of the present application provide a modified positive electrode material and a preparation method thereof, a positive electrode plate and a battery to solve at least one problem existing in the background technology.
[0005] In a first aspect, the present invention provides a modified positive electrode material, wherein the modified positive electrode material comprises a modified ternary positive electrode material, wherein the chemical formula of the modified ternary positive electrode material is Li (1-2a) Ni x Co y Mn z O2A 2a (BO3)a , wherein a+x+y+z=1, 0.001≤a≤0.05, x≥0.8; the A includes K and / or Na, the B includes Si and / or Te, part of the B is doped in the bulk phase of the modified ternary positive electrode material, and part of the B forms a solid solution doping on the surface of the modified ternary positive electrode material.
[0006] In conjunction with the first aspect of the present application, in an optional implementation manner, the modified positive electrode material further includes:
[0007] A coating agent is coated on at least a portion of the surface of the modified ternary positive electrode material; the molar ratio of the modified ternary positive electrode material to the coating agent is 1:(0.001-0.06); the coating agent includes an organic lithium salt.
[0008] In a second aspect, an embodiment of the present application provides a method for preparing a modified positive electrode material, the method comprising the following steps:
[0009] S1: Provide a precursor powder, the chemical formula of which is Ni x Co y Mn z (OH)2, where x+y+z=1;
[0010] S2: After mixing the precursor powder, the lithium source and the dopant, perform a first heat treatment to obtain a modified ternary positive electrode material; the dopant includes silicate and / or tellurate, part of the silicate and / or tellurate is doped in the bulk phase of the modified ternary positive electrode material, and part of the silicate and / or tellurate forms a solid solution doping on the surface of the modified ternary positive electrode material; the molar ratio of the precursor powder, the lithium source and the dopant is 1: (1~1.12): (0.001~0.05).
[0011] In conjunction with the second aspect of the present application, in an optional implementation manner, step S2 satisfies at least one of the following features (1) to (4):
[0012] (1) The lithium source includes at least one of lithium acetate, lithium nitrate, lithium sulfate, lithium chloride, lithium carbonate or lithium hydroxide;
[0013] (2) The dopant includes at least one of potassium silicate, sodium silicate, sodium tellurite or potassium tellurite;
[0014] (3) The first heat treatment comprises:
[0015] The precursor powder, the lithium source and the dopant are mixed and then calcined; wherein the calcination temperature is 600°C to 780°C, the time is 8h to 16h, and the heating rate is 2°C / min to 6°C / min;
[0016] (4) After the first heat treatment, cooling, crushing and sieving are performed to obtain the modified ternary positive electrode material, wherein the sieving is performed using a sieve with a mesh size of 100 to 200.
[0017] In conjunction with the second aspect of the present application, in an optional implementation manner, the providing of precursor powder in step S1 includes:
[0018] Mixing a nickel source, a cobalt source, a manganese source and a solvent to obtain a mixed solution;
[0019] Adding a pH regulator and a complexing agent to the mixed solution in sequence to obtain a precursor mixed solution;
[0020] The precursor mixed liquid is heated, washed with water, centrifuged and dried to obtain the precursor powder.
[0021] In conjunction with the second aspect of the present application, in an optional implementation manner, the method satisfies at least one of the following features (1) to (10):
[0022] (1) The nickel source includes at least one of nickel acetate, nickel nitrate or nickel sulfate;
[0023] (2) The cobalt source includes at least one of cobalt acetate, cobalt nitrate or cobalt sulfate;
[0024] (3) the manganese source includes at least one of manganese acetate, manganese nitrate or manganese sulfate;
[0025] (4) The solvent includes water;
[0026] (5) The complexing agent includes aqueous ammonia;
[0027] (6) The ratio of the molar number of the complexing agent added to the total molar number of metal ions in the precursor mixture is (1.2-1.5):1;
[0028] (7) The pH adjuster includes sodium hydroxide and / or potassium hydroxide;
[0029] (8) The pH of the mixed solution after adding the pH adjuster is 8 to 11;
[0030] (9) The temperature of the precursor mixture heating is 200°C to 600°C; in the water washing step, the mass ratio of solid to water is 1:(0.5~2); the water washing time is 10min~30min; the centrifugal frequency is 1000rpm~15000rpm; the drying temperature is 80°C~200°C; the drying time is 2h~8h;
[0031] (10) The molar ratio of the lithium source, nickel source, cobalt source and manganese source is (1-1.2): (0.8-0.95): (0.02-0.05): (0.001-0.05).
[0032] In conjunction with the second aspect of the present application, in an optional implementation manner, the method further includes:
[0033] The modified ternary positive electrode material is mixed with a coating agent and then subjected to a second heat treatment, so that the coating agent is coated on at least part of the surface of the modified ternary positive electrode material; the molar ratio of the modified ternary positive electrode material to the coating agent is 1: (0.001-0.06); the coating agent includes an organic lithium salt.
[0034] In conjunction with the second aspect of the present application, in an optional implementation manner, the second heat treatment comprises:
[0035] The modified ternary positive electrode material and the coating agent are mixed and then calcined; wherein the calcination temperature is 300°C~500°C, the time is 3h~6h, and the heating rate is 2°C / min~6°C / min; after calcination, cooling, crushing and sieving are carried out, wherein the sieving is carried out using a sieve of 200 mesh~500 mesh.
[0036] In a third aspect, an embodiment of the present application provides a positive electrode plate, which includes the modified positive electrode material as described in the first aspect or includes the modified positive electrode material prepared by the preparation method as described in the second aspect.
[0037] In a fourth aspect, an embodiment of the present application provides a battery, comprising the positive electrode plate as described in the third aspect.
[0038] Compared with the prior art, the embodiments of the present application have the following beneficial effects:
[0039] The modified positive electrode material and preparation method thereof, positive electrode sheet and battery provided in the embodiments of the present application, the modified positive electrode material includes a modified ternary positive electrode material, and the chemical formula of the modified ternary positive electrode material is Li (1-2a) Ni x Co y Mn z O2A 2a (BO3) a , where a+x+y+z=1, 0.001≤a≤0.05, x≥0.8; A includes K and / or Na, and B includes Si and / or Te. By doping silicate and / or tellurite on the basis of high nickel ternary materials, the growth of primary particles in the synthesis process of positive electrode materials can be inhibited, the mechanical toughness of the particles can be improved, thereby inhibiting the cracking of the particles of the modified positive electrode materials during the cycle process and enhancing the stability of the structure of the modified positive electrode materials; K +and / or Na + Replace part of Li in high nickel ternary materials + , which can reduce the mixing of cations and expand the interlayer spacing of the material layered structure, thereby increasing the diffusion coefficient of lithium ions and further improving the rate performance of the modified positive electrode material. 2- ) and / or tellurite (TeO3 2- ) is partially doped into the bulk of the high-nickel ternary material, and partially forms near-surface doping on the surface. Thus, on the one hand, SiO3 2- and / or TeO3 2- It can provide a three-dimensional channel network that is conducive to the migration of lithium ions, reduce the energy barrier for lithium ion diffusion, and further improve the rate performance of the modified cathode material. On the other hand, SiO3 2- and / or TeO3 2- When encountering a reducing agent, it can decompose into oxides to protect the modified positive electrode material from corrosion by the electrolyte solution, thereby improving the cycle performance.
[0040] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0042] Figure 1 A schematic diagram of a process for preparing a modified positive electrode material provided in an embodiment of the present application;
[0043] Figure 2 This is a scanning electron microscope image of the positive electrode material prepared in Comparative Example 1;
[0044] Figure 3 This is a scanning electron microscope image of the modified positive electrode material prepared in Example 3 of the present application;
[0045] Figure 4 This is a scanning electron microscope image of the modified positive electrode material prepared in Example 12 of the present application;
[0046] Figure 5 This is a scanning electron microscope image of the positive electrode material prepared in Comparative Example 1 after cycling;
[0047] Figure 6 This is a scanning electron microscope image of the modified positive electrode material prepared in Example 3 of the present application after cycling. DETAILED DESCRIPTION
[0048] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is described in detail by combining the accompanying drawings and listing specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on conventional experimental conditions. The reagents and raw materials used in the present invention are commercially available unless otherwise specified.
[0049] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.
[0050] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "one", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.
[0051] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.
[0052] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.
[0053] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.
[0054] During the long cycle of the battery, as the lithium is removed and inserted, the particles of the high-nickel ternary material frequently expand and contract, and the increase in internal stress of the particles can easily lead to cracks, especially at higher charging voltages, such as about 4.2V (relative to Li / Li +The transition of the two hexagonal phases (H2 and H3) at a voltage of 2.5V to 1.5V (reference electrode) causes anisotropic volume expansion, which in turn causes severe structural degradation, which has a serious impact on rate performance and cycle performance, thereby reducing the battery cycle life. In addition, the Ni in the high-nickel ternary material 2+ Accessible + The cation mixing of the layers occurs, leading to the formation of a rock-salt phase, which results in structural degradation and huge capacity loss.
[0055] In the related art, trace amounts of H2O in fluorinated carbonate-based liquid electrolyte solutions react with lithium hexafluorophosphate (LiPF6) to form PF6 - The reaction will generate corrosive hydrofluoric acid (HF), which will lead to a series of irreversible reactions such as dissolution of cathode transition metal ions, oxygen evolution on the cathode surface, corrosion of aluminum foil and damage to the CEI membrane. Ultimately, it will cause serious consequences such as gassing and a sharp shortening of the cycle life of the high-nickel ternary material system during high-temperature storage and circulation.
[0056] Based on this, the embodiment of the present application provides a modified positive electrode material, which includes a modified ternary positive electrode material, and the chemical formula of the modified ternary positive electrode material is Li (1-2a) Ni x Co y Mn z O2A 2a (BO3) a , wherein a+x+y+z=1, 0.001≤a≤0.05, x≥0.8; A includes K and / or Na, and B includes Si and / or Te.
[0057] By doping silicate and / or tellurite on the basis of high nickel ternary materials, the primary particle growth during the synthesis of the positive electrode material can be inhibited, and the mechanical toughness of the particles can be improved to offset the high internal strain, thereby inhibiting the cracking of the particles of the modified positive electrode material during the cycle process, enhancing the stability of the modified positive electrode material structure, and improving the cycle performance and rate performance; K + and / or Na + Replace part of Li in high nickel ternary materials + , which can reduce the mixing of cations, and because K + and / or Na + The radius is significantly larger than Li + The radius can also expand the interlayer spacing of the material layered structure, thereby increasing the diffusion coefficient of lithium ions and further improving the rate performance of the modified positive electrode material. 2- ) and / or tellurite (TeO3 2- ) is partially doped into the bulk of the high-nickel ternary material, and partially forms a solid solution near-surface doping on the surface. In this way, on the one hand, SiO3 2-and / or TeO3 2- It can provide a three-dimensional channel network that is conducive to the migration of lithium ions, reduce the energy barrier for lithium ion diffusion, and further improve the rate performance of the modified cathode material. On the other hand, SiO3 2- and / or TeO3 2- When encountering a reducing agent, it can decompose into oxides to protect the modified positive electrode material from corrosion by the electrolyte solution, thereby improving the cycle performance.
[0058] When the doping amount of silicate and / or tellurate is small, the effect of improving the rate performance and cycle performance of the modified positive electrode material is relatively limited. When the doping amount of silicate and / or tellurate is large, the excess silicate and / or tellurate cannot be effectively doped into the particles of the positive electrode material and the near surface of the particles, and will eventually be removed as impurities. Therefore, in the embodiment of the present application, 0.001≤a≤0.05, for example, a can be 0.01, 0.02, 0.03 or 0.04, which can significantly improve the rate performance and cycle performance of the modified positive electrode material.
[0059] It should be noted that the above-mentioned reducing agent refers to electrolyte substances (including ester substances). During the charge and discharge process of the battery, the positive electrode material continuously loses electrons, the valence increases, and the oxidizability increases. When the positive electrode material encounters the electrolyte, a redox reaction will occur. For example, when the dopant is potassium silicate, potassium silicate can be decomposed into SiO2 when encountering the reducing agent. SiO2 does not react with hydrofluoric acid and can play an isolating role, thereby reducing the corrosion of hydrofluoric acid on the CEI film on the surface of the modified positive electrode material.
[0060] In some embodiments, the modified positive electrode material may further include: a coating agent, coated on at least a portion of the surface of the modified ternary positive electrode material; the molar ratio of the modified ternary positive electrode material to the coating agent is 1:(0.001~0.06), for example, it may be 1:0.01, 1:0.02, 1:0.03, 1:0.04 or 1:0.05; the coating agent may include an organic lithium salt.
[0061] In the embodiment of the present application, the coating agent is coated on at least part of the surface of the modified ternary cathode material, which can inhibit the side reaction between the modified cathode material and the electrolyte, so that the surface of the modified ternary cathode material can be protected to a certain extent. When the organic lithium salt contacts a trace amount of water in the electrolyte solution, the formed solution is slightly alkaline, so the HF in the electrolyte can be effectively removed, thereby reacting with the doped SiO3 2- and / or TeO3 2- It plays a synergistic role to better protect the modified positive electrode material from corrosion by the electrolyte solution, thereby further improving the surface stability and cycle performance of the modified positive electrode material.
[0062] When the content of the coating agent is low, the effect of protecting the modified positive electrode material from corrosion by the electrolyte solution is relatively limited. When the content of the coating agent is high, the thicker coating layer formed is not conducive to the embedding and extraction of lithium ions, and is likely to affect the electrochemical performance of the battery. Therefore, in the embodiment of the present application, the molar ratio of the modified ternary positive electrode material to the coating agent is 1: (0.001~0.06). This can effectively protect the modified positive electrode material from corrosion by the electrolyte solution while ensuring the electrochemical performance of the battery.
[0063] It should be noted that the coating agent is coated on at least part of the surface of the modified ternary positive electrode material. The coating agent may only coat part of the surface of the modified ternary positive electrode material, or may coat the entire surface of the modified ternary positive electrode material.
[0064] In some specific embodiments, the capping agent may include at least one of lithium citrate, lithium acetate, or lithium tartrate.
[0065] The present application also provides a method for preparing a modified positive electrode material. Figure 1 The method for preparing the modified positive electrode material provided in the embodiment of the present application comprises the following steps:
[0066] Step S1: Provide a precursor powder, the chemical formula of which is Ni x Co y Mn z (OH)2, where x+y+z=1;
[0067] Step S2: Mix the precursor powder, lithium source and dopant and perform a first heat treatment to obtain a modified ternary positive electrode material; the dopant includes silicate and / or tellurite; the molar ratio of the precursor powder, lithium source and dopant is 1: (1~1.12): (0.001~0.05).
[0068] In an embodiment of the present application, a modified ternary positive electrode material doped with silicate and / or tellurate is obtained by subjecting the precursor powder, lithium source and dopant to a first heat treatment (e.g., calcination). Silicate and / or tellurate can inhibit the growth of primary particles during the synthesis of the positive electrode material, improve the mechanical toughness of the particles to offset the high internal strain, thereby inhibiting the cracking of the particles of the modified positive electrode material during the cycle, enhancing the stability of the structure of the modified positive electrode material, and improving the cycle performance and rate performance.
[0069] When the doping amount of silicate and / or tellurite is small, the effect on improving the rate performance and cycle performance of the modified positive electrode material is relatively limited. When the doping amount of silicate and / or tellurite is large, the excess silicate and / or tellurite cannot be effectively doped into the particles of the positive electrode material and the near surface of the particles, and will eventually be removed in the form of impurities. If the removal is not thorough, it may have an adverse effect on the performance of the modified positive electrode material. Therefore, in an embodiment of the present application, the molar ratio of the precursor powder, the lithium source and the dopant is 1: (1~1.12): (0.001~0.05), for example, it can be 1:1.12:0.01, 1:1.12:0.02, 1:1.12:0.03 or 1:1.12:0.04, which can significantly improve the rate performance and cycle performance of the modified positive electrode material.
[0070] It should be understood that all the features and advantages of the modified positive electrode material described in the above embodiments are also applicable to the preparation method of the modified positive electrode material in the embodiments of the present application, and will not be described one by one here.
[0071] In some embodiments, providing a precursor powder in step S1 may include the following steps: first, mixing a nickel source, a cobalt source, a manganese source, and a solvent to obtain a mixed solution; second, adding a pH adjuster and a complexing agent to the mixed solution in sequence to obtain a precursor mixed solution; further, heating, washing, centrifuging, and drying the precursor mixed solution to obtain a precursor powder.
[0072] In the embodiments of the present application, there is no particular restriction on the types of nickel source, cobalt source, and manganese source, and they can be selected according to actual needs.
[0073] “Nickel source” refers to a compound for providing metallic nickel. For example, the nickel source may include at least one of nickel acetate, nickel nitrate or nickel sulfate.
[0074] The "cobalt source" refers to a compound for providing metallic cobalt. For example, the cobalt source may include at least one of cobalt acetate, cobalt nitrate or cobalt sulfate.
[0075] The "manganese source" refers to a compound for providing metallic manganese. For example, the manganese source may include at least one of manganese acetate, manganese nitrate or manganese sulfate.
[0076] The embodiments of the present application have no particular restrictions on the specific types of solvents, pH adjusters and complexing agents, which can be selected according to actual needs.
[0077] Exemplarily, the solvent may include water, which has low cost, high safety for operators, convenient waste liquid treatment, and little pollution to the environment, and is therefore suitable for use in industrial production.
[0078] Exemplarily, the pH adjusting agent may include sodium hydroxide and / or potassium hydroxide. In some specific embodiments, after the pH adjusting agent is added, the pH of the mixed solution is 8 to 11, for example, 8.5, 9, 9.5, 10 or 10.5, etc., so that preparation can be made for the next step of adding the complexing agent. The amount of the pH adjusting agent added can be adjusted according to the target pH value, as long as a certain amount of the pH adjusting agent is added to make the pH value of the solution within the above range.
[0079] Exemplarily, the complexing agent may include ammonia water, for example. In some specific embodiments, the ratio of the number of moles of complexing agent added to the total number of moles of metal ions in the precursor mixture is (1.2~1.5):1, for example, it may be 1.3:1 or 1.4:1, etc. The amount of complexing agent added can be determined according to the total number of moles of metal ions in the precursor mixture. For example, if the precursor mixture includes nickel ions, cobalt ions and manganese ions, the ratio of the number of moles of complexing agent added to the total number of moles of nickel ions, cobalt ions and manganese ions is (1.2~1.5):1. In this way, it is conducive to the preparation of high-quality modified positive electrode materials.
[0080] In some specific embodiments, the temperature of the precursor mixture can be 200°C to 600°C, for example, 300°C, 400°C, 450°C or 500°C, etc. By controlling the heating temperature of the precursor mixture, it is helpful to obtain a precursor powder with excellent performance, thereby improving the performance of the modified positive electrode material finally obtained.
[0081] In some specific embodiments, in the above-mentioned water washing step, the mass ratio of solid to water can be 1:(0.5~2), for example, 1:1 or 1:1.5, etc.; the water washing time can be 10min~30min, for example, 15min, 20min or 25min, etc.; in this way, the pH adjuster and the complexing agent can be removed more thoroughly to obtain a precursor powder with higher purity.
[0082] In some specific embodiments, in the above centrifugation step, the centrifugation frequency may be 1000 rpm to 15000 rpm, for example, 2000 rpm, 5000 rpm, 8000 rpm, 10000 rpm or 12000 rpm, etc.;
[0083] In some specific embodiments, in the above-mentioned drying step, the drying temperature can be 80°C~200°C, for example, it can be 100°C, 120°C, 150°C or 180°C, etc.; the drying time can be 2h~8h, for example, it can be 3h, 4h, 5h, 6h or 7h, etc., so that the dryness of the obtained precursor powder can reach the desired value.
[0084] In the embodiments of the present application, there is no particular restriction on the type of lithium source, which can be selected according to actual needs.
[0085] “Lithium source” refers to a compound for providing metallic lithium. For example, the lithium source may include at least one of lithium acetate, lithium nitrate, lithium sulfate, lithium chloride, lithium carbonate, or lithium hydroxide.
[0086] In some embodiments, the molar ratio of the lithium source, the nickel source, the cobalt source and the manganese source can be (1-1.2): (0.8-0.95): (0.02-0.05): (0.001-0.05). It can be understood that the above ratios can be adjusted according to the ratios of the elements in the general formula of the pre-obtained target modified positive electrode material, that is, according to the ratios or contents of the elements in the modified positive electrode material.
[0087] In some embodiments, the dopant may include at least one of potassium silicate, sodium silicate, sodium tellurate, or potassium tellurate.
[0088] In the embodiment of the present application, K in the dopant + and / or Na + Replace part of Li in high nickel ternary materials + , which can reduce the mixing of cations and expand the interlayer spacing of the material layered structure, thereby increasing the diffusion coefficient of lithium ions and further improving the rate performance of the modified positive electrode material. 2- ) and / or tellurite (TeO3 2- ) is partially doped into the bulk of the high-nickel ternary material, and partially forms near-surface doping on the surface. Thus, on the one hand, SiO3 2- and / or TeO3 2- It can provide a three-dimensional channel network that is conducive to the migration of lithium ions, reduce the energy barrier for lithium ion diffusion, and further improve the rate performance of the modified cathode material. On the other hand, SiO3 2- and / or TeO3 2- When encountering a reducing agent, it can decompose into oxides to protect the modified positive electrode material from corrosion by the electrolyte solution, thereby improving the cycle performance.
[0089] In some embodiments, the first heat treatment in step S2 may include: mixing the precursor powder, the lithium source and the dopant and then calcining them, the calcination temperature may be 600°C~780°C, for example, 630°C, 650°C, 680°C, 700°C or 750°C, etc., the calcination time may be 8h~16h, for example, 10h, 12h, 13h, 14h or 15h, etc., the heating rate may be 2°C / min~6°C / min, for example, 3°C / min, 4°C / min or 5°C / min, etc.
[0090] In the embodiments of the present application, the calcination temperature, time and heating rate are closely related to the doping effect of the dopant. Within the above calcination temperature range, the calcination effect can be improved, thereby improving the performance of the prepared modified positive electrode material. In addition, by controlling the calcination temperature, it is helpful to improve the interface reaction of the material and further improve the cycle performance of the battery.
[0091] At the above calcination temperature, the calcination time is controlled within 8h~16h, which can make the calcination more sufficient, thereby further improving the performance of the obtained modified positive electrode material.
[0092] Under the above calcination temperature and / or calcination time, the heating rate is controlled at 2°C / min~6°C / min, which can improve the calcination efficiency while making the material heated more evenly, that is, making the temperature distribution inside the material more even.
[0093] In some embodiments, after the first heat treatment, cooling, crushing and sieving are performed to obtain a modified ternary positive electrode material, wherein the sieving can be performed using a sieve of 100-200 meshes. In this way, a modified ternary positive electrode material with a suitable particle size and excellent performance can be obtained.
[0094] In some embodiments, the preparation method of the modified positive electrode material may also include: mixing the modified ternary positive electrode material with the coating agent and then performing a second heat treatment so that the coating agent is coated on at least a portion of the surface of the modified ternary positive electrode material; the molar ratio of the modified ternary positive electrode material to the coating agent is 1:(0.001~0.06), for example, it can be 1:0.01, 1:0.02, 1:0.03, 1:0.04 or 1:0.05; the coating agent includes an organic lithium salt.
[0095] In the embodiment of the present application, the coating agent is coated on at least part of the surface of the modified ternary cathode material, which can inhibit the side reaction between the modified cathode material and the electrolyte, so that the surface of the modified ternary cathode material can be protected to a certain extent. When the organic lithium salt contacts a trace amount of water in the electrolyte solution, the formed solution is slightly alkaline, so it can effectively remove HF in the electrolyte, thereby reacting with the doped SiO3 2- and / or TeO3 2- It plays a synergistic role to better protect the modified positive electrode material from corrosion by the electrolyte solution, thereby further improving the surface stability and cycle performance of the modified positive electrode material.
[0096] When the content of the coating agent is low, the effect of protecting the modified positive electrode material from corrosion by the electrolyte solution is relatively limited. When the content of the coating agent is high, the thicker coating layer formed is not conducive to the embedding and extraction of lithium ions, and is likely to affect the electrochemical performance of the battery. Therefore, in the embodiment of the present application, the molar ratio of the modified ternary positive electrode material to the coating agent is 1: (0.001~0.06). This can effectively protect the modified positive electrode material from corrosion by the electrolyte solution while ensuring the electrochemical performance of the battery.
[0097] In some specific embodiments, the coating agent may include at least one of lithium citrate, lithium acetate or lithium tartrate.
[0098] In some embodiments, the second heat treatment may include: mixing the modified ternary positive electrode material and the coating agent and then calcining them, the calcination temperature may be 300°C~500°C, for example, 320°C, 350°C, 400°C or 450°C, etc.; the calcination time may be 3h~6h, for example, 3.5h, 4h, 4.5h, 5h or 5.5h, etc.; the heating rate may be 2°C / min~6°C / min, for example, 3°C / min, 4°C / min or 5°C / min, etc.
[0099] In the embodiments of the present application, the calcination temperature, time and heating rate are closely related to the coating effect of the coating agent. Within the above calcination temperature range, the coating effect can be enhanced, thereby improving the performance of the obtained modified positive electrode material. In addition, by controlling the calcination temperature, it is helpful to improve the interface reaction of the material and further improve the cycle performance of the battery.
[0100] At the above calcination temperature, the calcination time is controlled at 3h~6h, so that the coating agent can be better coated on the surface of the modified ternary positive electrode material, so as to further enhance the protective effect of the coating agent on the modified positive electrode material, thereby further improving the performance of the prepared modified positive electrode material.
[0101] Under the above calcination temperature and / or calcination time, the heating rate is controlled at 2°C / min~6°C / min, which can improve the calcination efficiency while making the material heated more evenly, that is, making the temperature distribution inside the material more even.
[0102] In some embodiments, cooling, crushing and sieving are performed after the second heat treatment, wherein the sieving is performed using a sieve of 200-500 meshes, so as to obtain a modified positive electrode material with suitable particle size and excellent performance.
[0103] Based on this, an embodiment of the present application further provides a positive electrode plate, comprising the modified positive electrode material described in any of the above embodiments or the modified positive electrode material prepared by the preparation method described in any of the above embodiments.
[0104] It should be understood that since the positive electrode plate in the embodiments of the present application includes the modified positive electrode material described in any of the above embodiments or includes the modified positive electrode material prepared by the preparation method described in any of the above embodiments, the beneficial effects of the modified positive electrode material described in any of the above embodiments are applicable to the positive electrode plate.
[0105] In some embodiments, the positive electrode plate may include a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer may include the modified positive electrode material described in any of the aforementioned embodiments.
[0106] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.
[0107] The present application has no particular restrictions on the preparation method of the positive electrode sheet, and any preparation method known in the art may be selected as long as the purpose of the present application can be achieved.
[0108] Based on this, an embodiment of the present application also provides a battery, including the positive electrode plate described in the above embodiment.
[0109] It should be understood that, since the positive electrode plate in the embodiment of the present application includes the positive electrode plate described in the above embodiment, the beneficial effects of the modified positive electrode material described in any of the above embodiments are applicable to the battery.
[0110] In some embodiments, the battery may be a secondary battery, and the secondary battery may be a lithium-ion secondary battery. Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0111] The technical solution of the present application is further described below in combination with a plurality of embodiments and comparative examples. Example 1
[0112] The preparation of the modified positive electrode material in this embodiment includes the following steps:
[0113] S101: In terms of metal elements, nickel nitrate hexahydrate, cobalt nitrate hexahydrate, and manganese nitrate hexahydrate are dissolved in water at a molar ratio of 90:7:3 to prepare a 2 mol / L mixed solution; a NaOH solution with a concentration of 8 mol / L is prepared to adjust the pH of the entire solution, and ammonia water with a concentration of 8 mol / L is prepared as a complexing agent solution;
[0114] S102: mixing the NaOH solution with the mixed solution, adjusting the pH value of the mixed solution to about 10; then mixing the complexing agent solution with the mixed solution, the molar ratio of the mixed solution (based on the total molar amount of the metal element) to the complexing agent being 1:1.3, stirring and mixing thoroughly, the stirring temperature being 85° C., and the rotation speed being 300 rpm, to obtain a precursor mixed solution;
[0115] S103: After the precursor mixture obtained in step S102 is continuously stirred for about 8 hours, the precursor mixture after the reaction is poured into an evaporating dish, and the solution is heated and evaporated on a heating platform (such as a universal furnace) at a temperature of 300°C until the solution forms a viscous colloid, and the heating is continued to burn to obtain a solid product, and the solid product is added to a beaker with water, and washed with water for 20 minutes, the mass ratio of the solid product to water is 1:2, and then the washed material is centrifuged at 1500rpm for 10 minutes and filtered, and the filter residue is dried at 150°C for 3 hours to obtain a precursor powder;
[0116] S104: Add the precursor powder, lithium source and dopant obtained in step S103 into a stirring tank, wherein the molar ratio of the precursor powder, lithium source and potassium silicate is 1:1.12:0.01, and the amount ratio of the lithium source satisfies [n(Li)] / [n(Ni)+n(Mn)]=1.1. Stir and mix thoroughly and then perform calcination. The calcination is performed in an oxygen-containing atmosphere (the volume proportion of oxygen is 95%), and the temperature is increased to 680°C at a heating rate of 3°C / min and sintered for 8h. Then, the calcined powder is cooled to room temperature, crushed, and sieved with a 100-mesh sieve to obtain a modified positive electrode material. Example 2
[0117] The preparation method of the modified positive electrode material in this embodiment is different from that in Embodiment 1 in that:
[0118] In step S104 , the molar ratio of the precursor powder, the lithium source and the potassium silicate is 1:1.12:0.02.
[0119] The other steps are the same as those in Example 1. Example 3
[0120] The preparation method of the modified positive electrode material in this embodiment is different from that in Embodiment 1 in that:
[0121] In step S104 , the molar ratio of the precursor powder, the lithium source and the potassium silicate is 1:1.12:0.03.
[0122] The other steps are the same as those in Example 1. Example 4
[0123] The preparation method of the modified positive electrode material in this embodiment is different from that in Embodiment 1 in that:
[0124] In step S104 , the molar ratio of the precursor powder, the lithium source and the potassium silicate is 1:1.12:0.04.
[0125] The other steps are the same as those in Example 1. Example 5
[0126] The preparation method of the modified positive electrode material in this embodiment is different from that in Embodiment 1 in that:
[0127] In step S104 , the molar ratio of the precursor powder, the lithium source and the potassium silicate is 1:1.12:0.05.
[0128] The other steps are the same as those in Example 1. Example 6
[0129] The preparation of the modified positive electrode material in this embodiment includes the following steps:
[0130] S201: In terms of metal elements, nickel nitrate hexahydrate, cobalt nitrate hexahydrate, and manganese nitrate hexahydrate are dissolved in water at a molar ratio of 90:7:3 to prepare a 2 mol / L mixed solution; a NaOH solution with a concentration of 8 mol / L is prepared to adjust the pH of the entire solution, and ammonia water with a concentration of 8 mol / L is prepared as a complexing agent solution;
[0131] S202: mixing the NaOH solution with the mixed solution, adjusting the pH value of the mixed solution to about 10; then mixing the complexing agent solution with the mixed solution, the molar ratio of the mixed solution (based on the total molar amount of the metal element) to the complexing agent being 1:1.3, stirring and mixing thoroughly, the stirring temperature being 85° C., the rotation speed being 300 rpm, to obtain a precursor mixed solution;
[0132] S203: After continuously stirring the precursor mixture obtained in step S202 for about 8 hours, pour the reacted precursor mixture into an evaporating dish, heat and evaporate the solution on a heating platform (such as a universal furnace), and continue heating at a temperature of 300°C until the solution forms a viscous colloid, continue heating to cause combustion, and obtain a solid product. The solid product is added to a beaker with water and washed with water for 20 minutes. The mass ratio of the solid product to water is 1:2. Subsequently, the washed material is centrifuged at 1500 rpm for 10 minutes and then filtered. The filter residue is dried at 150°C for 3 hours to obtain a precursor powder.
[0133] S204: adding the precursor powder and lithium source obtained in step S203 into a stirring tank, wherein the molar ratio of the precursor powder to the lithium source is 1:1.12, and the amount ratio of the lithium source satisfies [n(Li)] / [n(Ni)+n(Mn)]=1.1, and fully stirring and mixing, and then calcining. The calcination is carried out in an oxygen-containing atmosphere (oxygen accounts for 95% by volume), and the temperature is increased to 680°C at a heating rate of 3°C / min and sintered for 8h; then the calcined powder is cooled to room temperature, crushed, and sieved with a 100-mesh sieve to obtain a primary sintered powder;
[0134] S205: The primary sintered powder obtained in step S204 is mixed with lithium citrate and then subjected to secondary calcination. The molar ratio of the primary sintered powder to lithium citrate is 1:0.01. The calcination treatment is carried out in an oxygen-containing atmosphere (the volume proportion of oxygen is 95%), and the temperature is increased to 450°C at a heating rate of 3°C / min and sintered for 5 hours; then the calcined powder is cooled to room temperature, crushed, and sieved using a 300-mesh sieve to obtain a modified positive electrode material. Example 7
[0135] The preparation method of the modified positive electrode material in this embodiment is different from that in Embodiment 6 in that:
[0136] In step S205, the molar ratio of the primary sintering powder to lithium citrate is 1:0.02.
[0137] The other steps are the same as those in Example 6. Example 8
[0138] The preparation method of the modified positive electrode material in this embodiment is different from that in Embodiment 6 in that:
[0139] In step S205, the molar ratio of the primary sintering powder to lithium citrate is 1:0.03.
[0140] The other steps are the same as those in Example 6. Example 9
[0141] The preparation method of the modified positive electrode material in this embodiment is different from that in Embodiment 6 in that:
[0142] In step S205, the molar ratio of the primary sintering powder to lithium citrate is 1:0.04.
[0143] The other steps are the same as those in Example 6. Example 10
[0144] The preparation method of the modified positive electrode material in this embodiment is different from that in Embodiment 6 in that:
[0145] In step S205, the molar ratio of the primary sintering powder to lithium citrate is 1:0.05.
[0146] The other steps are the same as those in Example 6. Embodiment 11
[0147] The preparation method of the modified positive electrode material in this embodiment is different from that in Embodiment 6 in that:
[0148] In step S205, the molar ratio of the primary sintering powder to lithium citrate is 1:0.06.
[0149] The other steps are the same as those in Example 6. Example 12
[0150] The preparation method of the modified positive electrode material in this embodiment is different from that in Embodiment 6 in that:
[0151] In step S204, the raw material calcined is added with a dopant, and the molar ratio of the precursor powder, the lithium source and the dopant is 1:1.12:0.03;
[0152] In step S205, the molar ratio of the primary sintering powder to lithium citrate is 1:0.04.
[0153] The other steps are the same as those in Example 6.
[0154] Comparative Example 1
[0155] The preparation method of the modified positive electrode material in Comparative Example 1 is different from that in Example 6 in that:
[0156] The raw material for secondary calcination in step S205 does not contain lithium citrate, and the obtained positive electrode material is recorded as Li 1.02 Ni 0.90 Co 0.07 Mn 0.03 .
[0157] The other steps are the same as those in Example 6.
[0158] The positive electrode materials obtained in the above examples and comparative examples were made into lithium-ion batteries, and the performance of the batteries was tested. The details are as follows:
[0159] The modified positive electrode material, binder PVDF, and conductive carbon black (super-P) obtained in the above embodiments and comparative examples are added to a certain amount of NMP in a mass ratio of 90:6:4, stirred in a drying room to form a slurry, and the slurry is coated on aluminum foil. After drying and rolling, a positive electrode sheet is punched to obtain a disc with a diameter of 1.2 cm. The items required for the experiment are placed in an oven at 60°C for 12 hours of drying. Subsequently, a CR2032 button battery is assembled in an argon-protected glove box, wherein the negative electrode uses a purchased metal lithium sheet, and the electrolyte is a solution of 1 mol / L LiPF6 in a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1. The battery assembly order is negative electrode shell-metal lithium-diaphragm-positive electrode sheet-gasket-spring-positive electrode shell. After the battery assembly is completed and aged for 12 hours, charge and discharge tests at different potentials are carried out.
[0160] Performance testing of lithium-ion batteries, including:
[0161] (1) Capacity test:
[0162] 0.1C charging capacity: 0.1C constant current and constant voltage charging to 4.3V, the cut-off current is 0.05C, and it is left to stand for 5 minutes. The capacity measured in this step is the 0.1C charging capacity (recorded as C0).
[0163] 0.1C discharge capacity: Discharge at 0.1C constant current to 2.8V and let stand for 5 minutes. The capacity measured in this step is the 0.1C discharge capacity (denoted as C1).
[0164] The first coulomb efficiency (first efficiency) is: C1 / C0.
[0165] 2C discharge capacity: 0.1C constant current and constant voltage charging to 4.3V, the cut-off current is 0.05C, and 2C constant current discharge to 2.8V. The discharge capacity measured in this step is the 2C discharge capacity (denoted as C2).
[0166] The 2C discharge capacity ratio is: C2 / C1.
[0167] (2) Cyclic performance test (tested on the Xinwei system):
[0168] Charging: 1C constant current and constant voltage charging to 4.3V, cut-off current is 0.05C, and stand for 5 minutes; Discharging: 1C constant current discharge to 2.8V, stand for 5 minutes. Completing one charging and discharging process is considered to complete one cycle.
[0169] Discharge capacity after the first cycle of 1C operation: 1C constant current and constant voltage charging to 4.3V, the cut-off current is 0.05C, and 1C constant current discharge to 2.8V. The discharge capacity measured in this step is the discharge capacity of the first cycle of 1C operation (recorded as C3).
[0170] Discharge capacity when running at 1C to the 100th cycle: 1C constant current and constant voltage charging to 4.3V, the cut-off current is 0.05C, and 1C constant current discharge to 2.8V. The discharge capacity measured in this step is the discharge capacity when running at 1C to 100 cycles (recorded as C4).
[0171] After running 100 cycles at 1C, the capacity retention rate is: C4 / C3.
[0172] (3) Direct Current Resistance (DCR) test: 1C constant current and constant voltage charging to 4.3V, the cut-off current is 0.05C, the voltage is recorded as U0, 2C constant current discharge for 30s, the voltage is recorded as U1, DCR=(U0-U1) / I, I=2C1.
[0173] The test results of the battery performance are shown in Table 1.
[0174] It can be seen from the data in Table 1 that compared with the positive electrode material of Comparative Example 1, the modified positive electrode materials prepared in Examples 1 to 5 of the present application have a reduced particle size after being doped with potassium silicate (K2SiO3), and the median particle size Dv50 of the positive electrode material is relatively small, because silicate (SiO3 2- ) is doped into the bulk phase of high nickel ternary materials to replace the transition metal octahedron TMO6, which can inhibit the growth of primary particles, thereby significantly reducing the particle size of the finished particles and shortening the lithium ion migration path. + The radius is much larger than Li + The radius, K + Doping can expand the interlayer spacing of layered materials, increase the diffusion coefficient of lithium ions, and reduce the resistance of lithium ion migration. 2- It can provide a three-dimensional channel network that is conducive to the migration of lithium ions and reduce the energy barrier for lithium ion diffusion, which is manifested in the significant improvement of discharge capacity, first efficiency, and 2C rate discharge capacity ratio, and the reduction of DCR in the first cycle. K2SiO3 doping helps to improve the mechanical toughness of the modified positive electrode material particles to offset the high internal strain, inhibit the cracking of the particles of the modified positive electrode material during the cycle, and thus improve the cycle performance of the modified positive electrode material, which is manifested in the inhibition of DCR growth after 100 cycles and the improvement of cycle retention rate. In addition, SiO3 2- Part of it is doped into the bulk phase, and part of it forms a solid solution-type near-surface doping on the surface of the modified positive electrode material. If the added amount is too large, the excess part cannot be doped into the particles of the positive electrode material and the near-surface of the particles, and is eventually removed as an impurity.
[0175] Table 1
[0176]
[0177] From the results in Table 1, it can be found that in the range of 1 mol% to 5 mol% of the molar percentage of the dopant, 3 mol% potassium silicate doping can greatly improve the rate discharge performance and cycle retention rate and reduce the system DCR, which is a better doping ratio.
[0178] It can be seen from the data in Table 1 that the modified positive electrode materials prepared in Examples 6 to 11 of the present application, lithium citrate (C6H5Li3O7) is introduced during the secondary sintering, mainly playing a role in surface coating. As an organic lithium salt and a strong organic base, lithium citrate is alkaline when it comes into contact with water. Taking advantage of the fact that lithium citrate is slightly alkaline when it comes into contact with water, it can be used to remove HF and H2O in the electrolyte, assist in forming a thin and strong CEI film, and inhibit the side reactions between the modified positive electrode material and the electrolyte. The introduction of an appropriate amount can improve the first efficiency and cycle performance of the lithium battery and reduce the DCR. However, when the coating agent content is too large, because the formed coating layer is too thick, it is not conducive to the embedding and extraction of lithium ions, which will cause a decrease in the first efficiency and electrical performance. From the results in Table 1, it can be found that in the range of 1 mol% to 6 mol% of the molar percentage of the coating agent, 4 mol% is the optimal coating ratio of lithium citrate.
[0179] It can be seen from the data of Example 12 in Table 1 that under 3 mol % potassium silicate doping and 4 mol % lithium citrate coating, the capacity utilization and first efficiency can be maximized, the DCR can be reduced, and the rate performance and cycle performance can be improved.
[0180] Figure 2 This is a scanning electron microscope image of the positive electrode material prepared in Comparative Example 1. Figure 3 and Figure 4 They are scanning electron microscope images of the modified positive electrode materials prepared in Example 3 and Example 12 of the present application respectively.
[0181] In the embodiment of the present application, part of the silicate is doped into the bulk phase, and part of it is enriched on the surface of the modified positive electrode material, and lithium citrate forms a dot-like coating on the surface of the modified positive electrode material ( Figure 4 The white dots on the surface of the modified positive electrode material). Figure 3 and Figure 4 It can be seen that the particles of the modified positive electrode material prepared in the present application have good morphology and a dense surface. According to the statistics of the scanning electron microscope images, the particle size of the modified positive electrode material is 10 μm to 12 μm. Figures 2 to 4 It can be seen that potassium silicate doping and lithium citrate coating have no significant effect on the morphology of the modified positive electrode material.
[0182] Figure 5 This is a scanning electron microscope image of the positive electrode material prepared in Comparative Example 1 after cycling. Figure 6 This is a scanning electron microscope image of the modified positive electrode material obtained in Example 3 of the present application after cycling. Figure 5 It can be seen that after 100 cycles, the particles of the positive electrode material frequently expand and shrink during the process of lithium removal and lithium insertion, and the particles crack significantly due to uneven stress inside the particles. Compared with the positive electrode material prepared in Comparative Example 1, the number of cracks inside the particles of the modified positive electrode material prepared in Example 3 of the present application is significantly less after 100 cycles, indicating that potassium silicate doping can effectively improve the mechanical toughness of the particles to offset the high internal strain, inhibit the cracking of the particles of the modified positive electrode material during the cycle, thereby inhibiting the generation of new interfaces, reducing the electrolyte loss while inhibiting the growth of DCR during the cycle, which is consistent with the results in Table 1.
[0183] It should be noted that the modified positive electrode material embodiments, modified positive electrode material preparation method embodiments, positive electrode plate embodiments and battery embodiments provided in the present application belong to the same concept; the technical features in the technical solutions recorded in the embodiments can be arbitrarily combined without conflict.
[0184] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.
Claims
1. A modified positive electrode material, characterized in that: The modified positive electrode material includes a modified ternary positive electrode material, and the chemical formula of the modified ternary positive electrode material is Li (1-2a) Ni x Co y Mn z O2A 2a (BO3) a , wherein a+x+y+z=1, 0.001≤a≤0.05, x≥0.8; the A includes K and / or Na, the B includes Si and / or Te, part of the B is doped in the bulk phase of the modified ternary positive electrode material, and part of the B forms a solid solution doping on the surface of the modified ternary positive electrode material.
2. The modified positive electrode material according to claim 1, characterized in that The modified positive electrode material also includes: A coating agent is coated on at least a portion of the surface of the modified ternary positive electrode material; the molar ratio of the modified ternary positive electrode material to the coating agent is 1:(0.001-0.06); the coating agent includes an organic lithium salt.
3. A method for preparing a modified positive electrode material, characterized in that: The method comprises the following steps: S1: Provide a precursor powder, the chemical formula of which is Ni x Co y Mn z (OH)2, where x+y+z=1; S2: After mixing the precursor powder, the lithium source and the dopant, perform a first heat treatment to obtain a modified ternary positive electrode material; the dopant includes silicate and / or tellurate, part of the silicate and / or tellurate is doped in the bulk phase of the modified ternary positive electrode material, and part of the silicate and / or tellurate forms a solid solution doping on the surface of the modified ternary positive electrode material; the molar ratio of the precursor powder, the lithium source and the dopant is 1: (1~1.12): (0.001~0.05).
4. The method for preparing the modified positive electrode material according to claim 3, characterized in that: Step S2 satisfies at least one of the following characteristics (1) to (4): (1) The lithium source includes at least one of lithium acetate, lithium nitrate, lithium sulfate, lithium chloride, lithium carbonate or lithium hydroxide; (2) The dopant includes at least one of potassium silicate, sodium silicate, sodium tellurite or potassium tellurite; (3) The first heat treatment comprises: The precursor powder, the lithium source and the dopant are mixed and then calcined; wherein the calcination temperature is 600°C to 780°C, the time is 8h to 16h, and the heating rate is 2°C / min to 6°C / min; (4) After the first heat treatment, cooling, crushing and sieving are performed to obtain the modified ternary positive electrode material, wherein the sieving is performed using a sieve with a mesh size of 100 to 200.
5. The method for preparing the modified positive electrode material according to claim 3, characterized in that: The step of providing precursor powder in step S1 includes: Mixing a nickel source, a cobalt source, a manganese source and a solvent to obtain a mixed solution; Adding a pH regulator and a complexing agent to the mixed solution in sequence to obtain a precursor mixed solution; The precursor mixed liquid is heated, washed with water, centrifuged and dried to obtain the precursor powder.
6. The method for preparing the modified positive electrode material according to claim 5, characterized in that: The method satisfies at least one of the following features (1) to (10): (1) The nickel source includes at least one of nickel acetate, nickel nitrate or nickel sulfate; (2) The cobalt source includes at least one of cobalt acetate, cobalt nitrate or cobalt sulfate; (3) the manganese source includes at least one of manganese acetate, manganese nitrate or manganese sulfate; (4) The solvent includes water; (5) The complexing agent includes aqueous ammonia; (6) The ratio of the molar number of the complexing agent added to the total molar number of metal ions in the precursor mixture is (1.2-1.5):1; (7) The pH adjuster includes sodium hydroxide and / or potassium hydroxide; (8) The pH of the mixed solution after adding the pH adjuster is 8 to 11; (9) The temperature of the precursor mixture heating is 200°C~600°C; in the water washing step, the mass ratio of solid to water is 1:(0.5~2); the water washing time is 10min~30min; the centrifugal frequency is 1000rpm~15000rpm; the drying temperature is 80°C~200°C; the drying time is 2h~8h; (10) The molar ratio of the lithium source, nickel source, cobalt source and manganese source is (1-1.2): (0.8-0.95): (0.02-0.05): (0.001-0.05).
7. The method for preparing a modified positive electrode material according to any one of claims 3 to 6, characterized in that: The method further comprises: The modified ternary positive electrode material is mixed with a coating agent and then subjected to a second heat treatment, so that the coating agent is coated on at least part of the surface of the modified ternary positive electrode material; the molar ratio of the modified ternary positive electrode material to the coating agent is 1: (0.001-0.06); the coating agent includes an organic lithium salt.
8. The method for preparing the modified positive electrode material according to claim 7, characterized in that: The second heat treatment comprises: The modified ternary positive electrode material and the coating agent are mixed and then calcined; wherein the calcination temperature is 300°C~500°C, the time is 3h~6h, and the heating rate is 2°C / min~6°C / min; after calcination, cooling, crushing and sieving are carried out, wherein the sieving is carried out using a sieve of 200 mesh~500 mesh.
9. A positive electrode sheet, characterized in that: The positive electrode plate comprises the modified positive electrode material described in claim 1 or 2 or comprises the modified positive electrode material prepared by the preparation method described in any one of claims 3 to 8.
10. A battery, characterized in that: Including the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Manganese-based solid solution positive electrode material doped with anions and preparation method thereof
CN103500831A
Lithium-doped modified high-nickel low-cobalt ternary positive electrode material for lithium ion battery, and preparation method thereof
CN112768687A
High-nickel positive electrode material, preparation method thereof and battery
CN117832449A